Evaluation of serum concentrations of homocysteine using high-performance liquid chromatography for patients with Preeclampsia (Journal of Pharmaceutical Negative Results, 2022)
Preeclampsia is a condition that causes persistently high blood pressure during pregnancy or the postpartum period. It's frequently linked to excessive protein levels in the urine, new-onset blood platelet depletion, or indicators of brain difficulty including seizures and/or visual difficulties. It's detected by an increase in the expecting mother's blood pressure after the 20th week of pregnancy, and it's only seen in humans. Preeclampsia raises the risk of maternal and perinatal morbidity and death, whether it is isolated or combined with preexisting hypertension. Preventing maternal and fetal morbidity/mortality requires early detection of high-risk variables and biomarkers for preeclampsia. Preeclampsia causes pathophysiological changes both locally (defective placentation and decreased placental perfusion) and systemically (hypertension) (angiogenic imbalance and altered vascular endothelium function). Preeclampsia is characterized by an angiogenic imbalance, and angiogenic indicators might be useful tools for detecting and diagnosing afflicted pregnancies early on.